CD31hiEmcnhi Vessels Support New Trabecular Bone Formation at the Frontier Growth Area in the Bone Defect Repair Process - Jimeng Wang (Nature Portfolio, 2017)
Abstract CD31hiEmcnhi vessels were a subtype of vessels in the murine skeletal system, with high levels of platelet and endothelial cell adhesion molecule-1 (PECAM-1/CD31) and endomucin (Emcn). They were reported coupling angiogenesis and osteogenesis during bone development. We investigated the distribution of these vessels in rat tibiae and their temporal and spatial distribution during the bone defect repair process to improve our understanding of the importance of these vessels. We confirmed that CD31hiEmcnhi vessels were specially distributed around the trabecular bones near metaphysis and endosteum in rat tibiae. At 3 days post bone injury, CD31hiEmcnhi vessels proliferated and were extensively distributed across the entire repair area. At 7 and 14 days post-injury, these vessels decreased but were specially distributed around the growing trabecular bones near the frontier growth area, suggesting that these vessels support new bone formation. The distribution of CD31hiEmcnhi vessels and the transcriptions of Hif-1α and VEGFA, as well as BMP2 and Osterix decreased at 7 and 14 days post-injury under osteoporotic conditions, in combination with insufficient osteogenesis. Our research is of great significance to help understand the important role of CD31hiEmcnhi vessels in supporting new trabecular bones formation during bone defect repair process.